Progression‐associated molecular changes in basal/squamous and sarcomatoid bladder carcinogenesis. Issue 4 (24th February 2023) - Fontugne, Jacqueline; Wong, Jennifer; Cabel, Luc; Neyret‐Kahn, Hélène; Karboul, Narjesse; Maillé, Pascale; Rapinat, Audrey; Gentien, David; Nicolas, André; Baulande, Sylvain; Sibony, Mathilde; Bernard‐Pierrot, Isabelle; et al.
Abstract: The aggressive basal/squamous (Ba/Sq) bladder cancer (BLCA) subtype is often diagnosed at the muscle‐invasive stage and can progress to the sarcomatoid variant. Identification of molecular changes occurring during progression from non‐muscle‐invasive BLCA (NMIBC) to Ba/Sq muscle‐invasive BLCA (MIBC) is thus challenging in human disease. We used the N ‐butyl‐ N ‐(4‐hydroxybutyl)‐nitrosamine (BBN) mouse model of Ba/Sq MIBC to study longitudinally the molecular changes leading to the Ba/Sq phenotype and to the sarcomatoid variant using IHC and microdissection followed by RNA‐seq at all stages of progression. A shift to the Ba/Sq phenotype started in early progression stages. Pathway analysis of gene clusters with coordinated expression changes revealed Shh signaling loss and a shift from fatty acid metabolism to glycolysis. An upregulated cluster, appearing early in carcinogenesis, showed relevance to human disease, identifying NMIBC patients at risk of progression. Similar to the human counterpart, sarcomatoid BBN tumors displayed a Ba/Sq phenotype and epithelial–mesenchymal transition (EMT) features. An EGFR/FGFR1 signaling switch occurred with sarcomatoid dedifferentiation and correlated with EMT. BLCA cell lines with high EMT were the most sensitive to FGFR1 knockout and resistant to EGFR knockout. Taken together, these findings provide insights into the underlying biology of Ba/Sq BLCA progression and sarcomatoid dedifferentiation with potential clinical implications. © 2023 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of The Pathological Society of Great Britain and Ireland.